INTEGRASI E-LEARNING DENGAN MEDIA SOSIAL MENGGUNAKAN SINGLE SIGN ON SYSTEM - Pujianto Pujianto (IIB Darmajaya, 2013)
E-Learning has become a strategy and solution for agencies education and successful organizations in the world in order to regulate and updating of knowledge and learning. For its members, so that no less in an increasingly competitive competition in the era of globalization. When e-learning owned agencies or organizations can be integrated into social media then it would make learning process will be growing and very enjoyable. The method used in this study is to collect data needed to build e-learning and social media.The developed E-learning is using moodle cms and social media is using Mahara cms. E-learning online is developed by garuda-book.com address and cs-learning.com while social media developed to address janevela.com. This is the result of an empirically-based social media e-portfolio and e-learning are integrated with the method of single sign on. Users can access social media through e-learning that has developed. Respondents were involved in the testing of this system comes of students of informatics and informatics engineering management. Of the 100 respondents who were randomly selected to evaluate the developed social media that produces 100% the registration process easier,87% easy charging profile, charging 70% of e-portfolio is easy, 100% manufacture easy group, 72% of making blogs easy and 100% knowledge sharing Keywords: E-learning, social media, e-portfolios and Sigle Sign on